Inward-Outward Internationalization Patterns of Medium and Large-Sized Polish Firms During the Economic Transition - Witek-Hajduk, Marzanna (Studia Oeconomica Posnaniensia, 2017)
The aim of this paper is to answer the following question: What are the patterns of internationalisation of medium and large-sized Polish enterprises established after 1989 due to export and import linkages and in terms of the speed of internationalisation, the age of export, and the age of import. Telephone interviews using the CATI method were employed to collect data and 251 telephone interviews with respondents from Polish companies established after 1989 which employ 50 or more employees were completed. Three patterns of the internationalization of Polish companies have been identified: exporters who are not importers, exporters who are importers and importers who are not exporters. The surveyed companies are characterized by the low age and speed of export. There is a lack of significant differences between exporters who are not importers and exporters who are importers in terms of the age of export and the speed of export.